PROSPECTS FOR THE USE OF VIRTUAL HERBARIUM IN PROFESSIONAL PREPARATION OF FUTURE BIOLOGY TEACHERS (EDUCATION IN THE 21ST CENTURY, 2023)
The essence and role of electronic (virtual) herbarium are considered. Identified property advantages and disadvantages of virtual herbarium as a means of visual aids. The possibility of using a virtual herbarium in the educational process of graduate schools in the study of the discipline of the professional cycle of preparation of biology teacher is determined.Electronic herbaria (EG), or, as they are also called virtual, can both protect valuable specimens and increase the access of all interested to catalogs and virtual herbarium bases. The electronic virtual herbarium is an information resource that provides fast and high-quality access to updated and open databases and is the highest level of accumulation, storage and distribution of textual and graphical information. The ЕG has several advantages: it prevents damage to unique samples; provides cost-effectiveness and ergonomics, which is manifested in saving time and money; speed and convenience; availability; updatability; the ability to search and analyze.The lack of use of EG is the possibility of loss of diagnostic features of plant; using with visual purpose only; limited possibilities with the capacity of the server of the institution; the need for high-quality expensive equipment for digitization; effort to digitize large herbarium funds.EG is possible and necessary in teaching educational disciplines from the professional cycle “Botany with the basics of geobotany”, “Basics of agriculture”, “Plant physiology”, “Plant ecology”, “Medical plants”, “Basics of ecology” and etc.The prospect of further research is the full digitization of the herbarium fund of the Department of Botany and Ecology of KSPU and the introduction of EG in electronic training courses of professional training disciplines on the basis of the university-wide platform Moodle.
Keywords: virtual herbarium, professional training, biology teacher, visibility